Coffee Shop Business Performance As Deduction of Motivation and Innovation - CHRISTANTYO, E. Hartojo; SHIRATINA, Aldina (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to analyze the performance of the coffee shop business and identify the factors that influence it and their relationship with the motivation and innovation of coffee shop workers during the Covid-19 pandemic. This research is directed to determine the relationship between variables that have an influence on business performance and competitiveness as an indicator of marketing carried out by coffee shops which are included in the micro, small and medium enterprises (MSMEs) to maintain and improve their business performance, through motivation and innovation through mediation. Competitiveness based on descriptions and previous studies. The population of this non-franchise coffee shop study is estimated at 150 coffee shops. Hence, the researchers used the Google form to determine a random sample of 103 coffee shops in the Tangerang and South Tangerang areas. The data analysis method uses the Structural Equation Model-Partial Least Square (SEM-PLS). The study's results found that the motivation of MSME coffee shop entrepreneurs during the Covid-19 pandemic was not statistically significant either directly or indirectly. The study's results found that the motivation of MSME coffee shop entrepreneurs during the Covid-19 pandemic was not statistically significant either directly or indirectly. The study's results found that the motivation of MSME coffee shop entrepreneurs during the Covid-19 pandemic was not statistically significant either directly or indirectly. In contrast, the innovations made by coffee shop entrepreneurs proved to affect the business performance of their coffee shops significantly. The implications of this research are discussed in full in the article.